BEL UMURTQALARIDA DISKEKTOMIYADAN KEYINGI DISK CHURRALARI QAYTALANISHI SABABLARI TAHLILI - Mamajanov B.S, Qodirov D.R (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Recurrent lumbar disc herniation after surgical intervention is a prevalent issue, posing a significant challenge in healthcare. Studies indicate that patients with a higher risk of recurrence often present with demographic factors (age, sex differences), anatomical variations, lifestyle factors, and BMI as primary risk factors. Additionally, chronic conditions such as diabetes and smoking further elevate the likelihood of recurrence. A comprehensive assessment and personalized treatment plans are essential to improve patient outcomes, minimize chronic disability, and prevent recurrence.